Trust, Distrust and Control Interplay in Interorganizational Relations - Agnieszka Padzik-Wołos (European Management Studies)
Purpose: The purpose of this paper is to provide a systematic literature review of research on the interplay between trust, distrust and control in interorganizational relations. The authors aim at diagnosing the current state of research along with gaps in the literature and then outlining opportunities for further research. The paper fulfills the aims by exploring the literature in four fields: (1) the understanding of trust, distrust and control, (2) interplay between trust and control, (3) relation between control and distrust and (4) relation between trust, distrust and control. Design/methodology/approach: The systematic literature review was conducted following the framework in Kraus et al. (2020). The sample consisted of 78 publications which were analyzed both quantitatively and qualitatively. Findings: Our systematic literature review revealed the prevalence of debate on trust, with distrust being marginalized. Five research gaps emerged from the analysis. As for the relation between two constructs, the trust – control debate is on top, trust – distrust takes the second position, with distrust – control as a marginal research area. Originality/value: The paper is a comprehensive review of the body of literature integrating three constructs: trust, distrust and control, along with new research directions.